Alkaline Water Splitting: NiFe/(Ni, Fe)3S2 Core/Shell Nanowire Arrays as Outstanding Catalysts for Electrolytic Water Splitting at High Current Densities (Small Methods 10/2019). Issue 10 (15th October 2019) - Hsieh, Cheng‐Ting; Chuah, Xui‐Fang; Huang, Chun‐Lung; Lin, Hao‐Wei; Chen, Yu‐An; Lu, Shih‐Yuan
Abstract : In article1900234 by Shih‐Yuan Lu and co‐workers, NiFe/(Ni, Fe)3 S2 core/shell nanowire arrays, fabricated with an anodic aluminum oxide membrane templated electrodeposition followed by sulfur ion exchange, are developed as an outstanding catalyst for oxygen evolution reaction, achieving an ultralow overpotential of 305 mV at a high current density of 400 mA cm −2 . The nanowire array‐based electrode proves to be a promising new catalyst architecture design for electrocatalytic processes.